The State Financial Recovery on Criminal Acts of Corruption through Approach to Criminal Claim - Fidianto, Grahita; Ma'ruf, Umar; Witasari, Aryani (Universitas Islam Sultan Agung, 2021)
The purpose of this study is to find out and analyze the practice of imposing additional criminal charges in the form of payment of compensation, and how the concept of recovering state financial losses based on asset confiscation in the Corruption Crime Act. The method used in writing this law uses a normative juridical approach. The results of this study are that the practice of recovering state financial losses through additional criminal penalties in the form of payment of compensation is still limited to articles containing elements of state financial losses, while the level of success depends on the level of awareness or willingness of the convict to pay. The imposition of additional crimes in the form of confiscation of the convict's assets is not limited to corruption offenses with elements of state financial losses, and the success rate depends on the ability of the investigator to collect the convict's assets related to corruption, as well as the ability of the public prosecutor to prove the corruption-related property during the trial.